BALIQLARDA TRIXODINOZ KASALLIGINING EPIZOOTOLOGIYASI, DAVOLASH USULLARI VA OLDINI OLISH CHORALARI - Alimov , A.Sh.; Bobonazarov, E.I. (Educational Research in Universal Sciences, 2023)
This article describes the epizootology, clinic, distribution and development of trichodinosis, one of the ciliated ciliates, which is common among juvenile fish in our fish ponds and causes serious damage to them, as well as modern measures for the treatment and prevention of this disease.